Efficacy of FimA antibody and clindamycin in silkworm larvae stimulated with Porphyromonas gulae. Issue 1 (1st January 2021) - Yoshida, Sho; Inaba, Hiroaki; Nomura, Ryota; Murakami, Masaru; Yasuda, Hidemi; Nakano, Kazuhiko; Matsumoto-Nakano, Michiyo
ABSTRACT: Objective : Porphyromonas gulae, a major periodontal pathogen in animals, possesses fimbriae that have been classified into three genotypes (A, B, C) based on the diversity of fimA genes encoding fimbrillin protein (FimA). P. gulae strains with type C fimbriae were previously shown to be more virulent than other types. In this study, we further examined the host toxicity mediated by P. gulae fimbriae by constructing recombinant FimA (rFimA) expression vectors for each genotype and raised antibodies to the purified proteins. Methods and Results : All larvae died within 204 h following infection with P. gulae type C at the low-dose infection, whereas type A and B did not. Among fimA types, the survival rates of the larvae injected with rFimA type C were remarkably decreased, while the survival rates of the larvae injected with rFimA type A and type B were greater than 50%. Clindamycin treatment inhibited the growth of type C strains in a dose-dependent manner, resulting in an increased rate of silkworm survival. Finally, type C rFimA-speciﬁc antiserum prolonged the survival of silkworm larvae stimulated by infection with P. gulae type C strain or injection of rFimA type C protein. Conclusion : These results suggested that type C fimbriae have high potential for enhancement of bacterial pathogenesis, and that both clindamycin and anti-type C rFimA-specific antibodies are potent inhibitors of type C fimbriae-induced toxicity. This is the first report to establish a silkworm infection model using P. gulae for toxicity assessment.